The Influence of "PATUH"-Based Health Education on Health Management Efforts for Elderly Hypertension Sufferers in Sumberrejo Trucuk Village, Bojonegoro - Ahmad Zainal Abidin; Adhe Anniza Pramesti (Jurnal EduHealth, 2026)
Hypertension is a condition in which blood pressure in the arteries continuously increases. High blood pressure can cause additional stress on the heart and blood vessels, which in turn can increase the risk of various serious health problems, including heart attack, stroke, kidney failure, and other problems. Blood pressure is measured with two numbers: systolic pressure (pressure when the heart contracts) and diastolic pressure (pressure when the heart rests between contractions). The aim of the research is to analyze the influence of "obedience"-based health education on efforts to manage the health of elderly people suffering from hypertension in Sumberrejo Trucuk Bojonegoro Village. The research method in this study was to use a pre-experimental approach with a one-group pre-posttest design. The sample used was 34 respondents using a total sampling technique, then the research data was tested using a paired t-test. The results of this research show that there is a significant influence from providing "PATUH"-based health education on efforts to manage the health of elderly people with hypertension with a value of sig.0.002. This shows that the health management of hypertensive elderly people must pay attention to cognitive and other aspects as a form of an adequate healthy lifestyle